Highly Enantioselective Asymmetric Michael Addition Reactions with New Chiral Multisite Phase-Transfer Catalysts - Jayaraman, Sivamani; Kumaraguru, Duraimurugan; Arockiam, Jesin Beneto; Paulpandian, Subha; Rajendiran, Balasaravanan; Siva, Ayyanar (Synlett, 2014)
Highly enantioselective Michael addition reactions of diethyl malonate to various chalcones have been achieved under mild chiral multisite phase-transfer reaction conditions by the successful utilization of 2,4,6-(triscinchoniummethyl)phenyl-1,3,5-triazines as new chiral quaternary ammonium catalysts. This simple asymmetric Michael addition process was found to be quite effective and to obtain Michael adducts with very good yields and enantiomeric excesses.
Keywords: phase-transfer catalysts; Michael reaction; enantioselective reaction; quaternary ammonium salt; cinchona alkaloid